Making 'better stem' happen: the role of the MaSciL project - Newton, Len; Sorensen, Peter (The Association for Science Education, 2015)
‘Too often in secondary schools, science has seemed to students, parents and teachers to be quite separate from the rest of the curriculum and from the realities of everyday life; it has often seemed remote, clinical and inaccessible. The unique and distinctive features of science have, perhaps, been emphasised to such a degree that they have served to isolate the subject, making it difficult for all but a minority of students to gain much pleasure or satisfaction from its study’(Secondary Science Curriculum Review (SSCR), 1987, p.1). This paper describes aspects of Project ‘MaSciL’ (Mathematics and Science for Life), which is aimed at promoting the widespread use of inquiry-based science teaching in primary and secondary schools in Europe by connecting mathematics and science education to the world of work. MaSciL is one of several recent European Community (EC)-funded projects aimed at promoting a widespread use of inquiry-based science education (IBSE). Here, we explain the broader context in which the MaSciL project is located. Next, we examine the particular focus of the Project on the ‘world of work’ (WoW) and describe the development of a professional development toolkit for use with pre and in-service mathematics and science teachers. We describe how the toolkit can help to support professional learning communities (PLCs) of science teachers and, finally, we consider how the MaSciL project can serve to support developments in science teacher education in England.